Transformative systemic changes to embed environmental sustainability in foodservices: A grounded theory exploration. Issue 2 (20th March 2023) - Smeltzer, Madison E.; Davidson, Alexandra R.; Reidlinger, D. P.; MacKenzie‐Shalders, Kristen L.
Abstract: Aims: Foodservices are a strong contributor to global environmental impact. Systemic change is required to lead the transformation towards environmentally sustainable foodservices. However, guidance to support foodservices to be more environmentally sustainable is lacking. The aim was to explore food‐related environmentally sustainable strategies and their transferability to foodservices in a range of settings, to inform a framework for future application and research. Methods: A constructivist grounded theory study design was used. Semi‐structured interviews with foodservice sustainability consultants, who support foodservice organisations to improve environmental sustainability, were conducted. Interviews were recorded, transcribed, and coded line‐by‐line. Ten consultants were purposively sampled for diversity in location, organisation type, funding model, and services provided. Codes were collapsed into categories, to inform the development of themes and a framework for the implementation of strategies. Results: Four sub‐themes were created under an overarching theme of 'Transforming the Foodservice System': embedding leadership, shifting perspective, constructing collaborative networks, and fostering momentum. A range of implementation strategies were captured within the sub‐themes. Conclusion: These themes informed the development of a practical application framework for implementing sustainable strategies in foodservices that is useful for practice and future research in the area.